Society And The State In The Pandemic Context - A. Kosolapova, Natalya (2021)
The coronavirus infection pandemic affected all spheres of human existence, making it impossible to implement traditional regulation of socially significant, political and legal issues. Based on the importance of an unprecedented new reality, the authors were tasked with studying and analyzing the problems of interaction between the State and society in the context of the pandemic and the introduction of state measures to prevent the spread of viral infection, which to a degree or another limit the rights and freedoms of a person and citizen.